Simplified analytical procedure to calculate the impact behaviour of steel parking-structure columns. (December 2022) - Xiang, Siyu; He, Yongjun; Zhou, Xuhong
Abstract: The steel supporting frame of automatic mechanical garages is called a parking structure. Presently, for these novel structures, the design codes are without giving detailed guidelines to predict the response of their impacted column. Thus, this paper presents a simplified analytical procedure to calculate the impact behaviour of the column. The proposed method is based on the co-rotational rigid body model and follows the energy-balance principle. Compared with the previous analytical method, it specially targets the parking-structure column and can be used to conveniently and quickly calculate the column transverse displacement with considering the effects of the surrounding structural members and axial loads on the column. The research covers the situation where the column is subjected to the impacts at a low velocity, critical velocity, and overcritical velocity. Primarily, an approach is developed to simplify the overall parking structures. On that basis, the calculation formula for the critical impact velocity, i.e. the velocity that results in the formation of plastic hinges in the column, is derived. To predict the behaviour of the column under the impact beyond the critical impact velocity, the simplified analytical procedure is provided and then its accuracy is examined by validated numerical models. Eventually, according to the procedure, some suggestions are given to improve the design of the column after parametric analyses. It is recommended that control the axial-load levels of the column, particularly the column with a small section area, as well as set stiffeners on the column within the height of 1000 – 1500 mm.